Passivation method for improving phase stability of wide-band-gap perovskite
By using negative monovalent anion passivator to passivate the perovskite grain boundaries, the efficiency attenuation problem caused by the separation of iodine/bromide ion in wide-bandgap perovskite solar cells is solved, and the photophotographic stability and efficiency of the material are significantly improved.
Patent Information
- Application Number
- CN202510051778.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-25
AI Technical Summary
Under continuous light, the phase separation of iodine/bromide ions in wide-bandgap perovskite solar cells leads to continuous attenuation of device efficiency, making it difficult to improve the photophotographic stability of the material.
Negative monovalent anion passivator is used to passivate the perovskite grain boundaries to fill the vacancies of halogen anion on the perovskite surface, preventing the movement of iodine ions to the perovskite surface, thereby inhibiting the phase separation of iodine/bromide ions.
It significantly improves the ion moving activation energy of wide-bandgap perovskites, inhibits the phase separation of iodine/brominate ions, and improves photophotographic stability and photoelectric conversion efficiency.
Smart Images

Figure CN119894335A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of perovskite materials, and in particular relates to a passivation method for improving the stability of a wide bandgap perovskite phase, wherein the stability of the wide bandgap perovskite phase is improved by passivating halogen ion vacancy defects. Background Art
[0002] In the field of new photovoltaic solar cells, organic-inorganic hybrid perovskite solar cells have become a research hotspot in the photovoltaic field due to the outstanding photoelectric properties of perovskite materials (such as high light absorption coefficient, high carrier mobility, low exciton separation energy, strong defect tolerance, etc.) and low-cost processability (such as solution preparation method). With the improvement of the photoelectric conversion efficiency of single-junction perovskite photovoltaic cells (now the certified efficiency has exceeded 26%), the photoelectric conversion efficiency of single-junction devices has approached the theoretical limit (about 33%). At the same time, in order to break through the theoretical limitations of single-junction cells, scientific research and industry have developed new tandem cell devices such as perovskite / crystalline silicon tandem solar cells and all-perovskite tandem solar cells. Among them, the certified efficiency of all-perovskite tandem solar cells has exceeded 30%, which is about to exceed the Shockley-Queisser theoretical efficiency limit of single-junction photovoltaic cells, becoming a new hotspot for high-efficiency photovoltaic cells.
[0003] In the tandem battery, the wide bandgap perovskite subcell is a key component of the tandem battery. The bandgap width of the wide bandgap perovskite material is about 1.7eV to 1.8eV, and the halogen ions in the material components are composed of two ions: iodine and bromine. In the wide bandgap perovskite crystal, the iodine and bromine ions are evenly mixed and distributed throughout the crystal. However, under the continuous irradiation of AM 1.5 simulated sunlight, the iodine and bromine ions will migrate in a directional manner and form an iodine-rich perovskite region with a narrow bandgap and a bromine-rich perovskite region with a wide bandgap. The perovskite photophase separation is microscopically manifested as the movement of iodine and bromine ions. As the illumination time increases, an iodine-rich phase (bandgap narrowing region) and a bromine-rich phase (bandgap widening region) are formed. Scientific research shows that the main reason for the movement of iodine and bromide ions is the halogen vacancy defects distributed on the crystal surface and grain boundaries; and in the early stage of phase separation, the iodine ions moving to the grain boundaries are oxidized to form iodine element, which will further catalyze and accelerate the speed of phase separation. From the perspective of device performance, as the iodine / bromide ion phase separation process intensifies, the device efficiency will continue to decay. In order to improve the performance stability of wide-bandgap perovskite cells under continuous illumination, effective measures must be taken to inhibit the phase separation of iodine / bromide ions in wide-bandgap perovskites.
[0004] From the perspective of phase separation mechanism, the halogen ion vacancy defects on the interface and surface are the main reasons for inducing the migration of iodine / bromide ions; and the direction of ion migration phase separation is that iodine ions tend to be enriched on the surface of perovskite crystals, while bromide ions tend to migrate to the interior of the crystals. Further, studies have found that iodine ions that migrate to the surface of the crystal tend to capture holes to form iodine (I2) and iodine trianions (I3 - ), thereby accelerating the phase separation process. Summary of the invention
[0005] Based on the above theoretical research on the phase separation process, the present invention proposes a method for passivating the perovskite grain boundaries using a negative monovalent anion passivator. This type of material can be coated on the perovskite surface and grain boundaries during the perovskite crystallization process. On the one hand, this type of material can fill the halide anion vacancies on the perovskite surface and passivate defects; on the other hand, this type of material has a stronger binding force with lead ions than iodine ions, so it can prevent iodine ions from moving to the surface of the perovskite. Based on the above two aspects, the method proposed by the present invention can increase the activation energy of ion movement of wide-bandgap perovskites and greatly inhibit the iodine / bromide ion phase separation of wide-bandgap perovskites.
[0006] The characteristics of the passivating agent used in the method of the present invention include:
[0007] 1. The passivating agent is an ionic compound, wherein the anion valence is negative one, the ion radius is greater than 0.22nm, and does not contain halogen ions;
[0008] 2. The passivator does not react chemically with the perovskite precursor solution, but its anion reacts with Pb 2+ Ions have strong binding forces;
[0009] 3. The molecular weight of the passivating agent does not exceed 400 g / mol.
[0010] The functional group of the passivator usually needs to contain one or more atoms of oxygen, sulfur, phosphorus, etc. Based on the above screening principle, the present invention selects a series of benzoate passivators, specifically including: one or more combinations of benzoic acid metal salts such as sodium benzoate, potassium benzoate, calcium benzoate, zinc benzoate, or ammonium benzoate.
[0011] In a first aspect, the present invention provides a method for preparing a wide bandgap perovskite precursor solution, comprising the following steps:
[0012] S1: Dissolve formamidinium iodine (FAI), formamidinium bromide (FABr), cesium iodide (CsI), cesium bromide (CsBr), lead iodide (PbI2), and lead bromide (PbBr2) in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) according to the molar ratio, heat and stir to obtain FA 0.8 Cs0.2 Pb(Br 0.4 I 0.6 )3Perovskite precursor, filtration;
[0013] S2: adding the passivator powder having the above characteristics into the perovskite precursor, stirring until dissolved, and obtaining a wide bandgap perovskite precursor solution.
[0014] In some embodiments, the passivating agent is selected from metal benzoate salts, ammonium benzoate salts, or combinations thereof.
[0015] In some embodiments, the passivating agent is selected from sodium benzoate, potassium benzoate, calcium benzoate, zinc benzoate or a combination thereof.
[0016] In some embodiments, in step S1, the volume ratio of DMF to DMSO in the mixed solvent is 3:1.
[0017] In some embodiments, in step S1, FA 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 The perovskite precursor was filtered using a 0.22 μm PTFE filter.
[0018] In some embodiments, in step S2, the amount of the passivating agent added is 0.10-5.00 mol % of the molar mass of the perovskite precursor.
[0019] In a second aspect, the present invention provides a method for preparing a wide bandgap perovskite solar cell, comprising the following steps:
[0020] Step 1: ultrasonically clean the conductive glass ITO substrate with water, acetone and isopropanol in sequence; blow dry the cleaned ITO substrate with a nitrogen gun, and then treat the substrate with ultraviolet ozone for 15 minutes; spin-coat the aqueous dispersion of nickel oxide nanoparticles on the substrate, and move it to a heating table to complete annealing treatment to prepare a nickel oxide hole transport layer; further, spin-coat the solution of the monomolecular self-assembled layer on the nickel oxide hole transport layer, and complete heating annealing treatment to prepare a composite hole transport layer;
[0021] Step 2: adding a passivating agent to the perovskite precursor solution and stirring until completely dissolved, wherein the passivating agent is selected from metal benzoate, ammonium benzoate or a combination thereof;
[0022] Step 3: Spin-coat the perovskite precursor solution on the surface of the composite hole transport layer prepared in step 1 by spin coating, and move it to a heating table to complete annealing treatment to prepare a perovskite film;
[0023] Step 4: Using vacuum thermal deposition technology, C60, BCP and Cu electrode materials are sequentially deposited on the surface of the perovskite film prepared in step 3 to obtain a wide bandgap perovskite solar cell.
[0024] In some embodiments, in step 1, the concentration of the aqueous dispersion of nickel oxide nanoparticles is 10 mg / mL, the spin coating parameters are 4000 rpm, the time is 30 seconds, and the annealing conditions are 150° C., and the time is 30 minutes.
[0025] In some embodiments, in step 2, the amount of the passivating agent added is 0.10-5.00 mol % of the molar mass of the perovskite precursor.
[0026] In some embodiments, in step 2, the perovskite precursor solution is FA 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 solution.
[0027] In some embodiments, in step 3, the concentration of the perovskite precursor solution is 1.4 mol / L. The spin coating method is: one-step anti-solvent method, 5000 rpm, time 40 seconds, and 200 μL of chlorobenzene is added as anti-solvent at the 30th second, and the annealing condition is 100° C., time 10 minutes.
[0028] In some embodiments, in step 4, the thicknesses of the C60, BCP and Cu electrodes are 20 nm, 5 nm and 100 nm, respectively.
[0029] In a third aspect, the present invention provides a wide bandgap perovskite solar cell obtained by the above preparation method.
[0030] The structure of the wide bandgap perovskite solar cell is as follows Figure 1 As shown, there are an ITO conductive substrate, a hole transport layer, a perovskite layer, an electron transport layer and a metal electrode layer in sequence.
[0031] In some embodiments, the wide bandgap perovskite film and wide bandgap perovskite solar cell prepared by the above method have significantly improved photo stability and sustained illumination efficiency stability.
[0032] In a fourth aspect, the present invention provides the use of the perovskite precursor solution in the preparation of a perovskite solar cell.
[0033] Technical Effects
[0034] The present invention provides a simple and easy-to-use method for improving the light stability of wide band gap perovskite cells, using an anion passivator with stronger binding force with lead ions on the surface of perovskite to coat the surface of perovskite, fill the surface halogen vacancies, and prevent iodine ions from moving to the crystal surface, thereby effectively inhibiting the phase separation of wide band gap perovskite. By directly dissolving a series of passivators such as sodium benzoate and potassium benzoate in a perovskite precursor solution, and preparing according to the conventional spin coating process of perovskite devices, a wide band gap perovskite film and a battery device with excellent photographic stability can be obtained. From the theoretical characterization, this series of passivators can greatly improve the ion movement activation energy of the perovskite film; and can effectively inhibit the process of iodine ions escaping from the perovskite crystal and oxidizing to iodine element. On the other hand, the anion part in the passivator can be combined at the perovskite grain boundary and the crystal surface, playing a role in surface and interface defect passivation. This novel and simple passivation strategy can significantly improve the photoelectric conversion efficiency and photographic stability of wide band gap perovskite photovoltaic devices.
[0035] The passivation strategy proposed in the present invention significantly reduces the ideal factor of the wide bandgap perovskite voltage, indicating that the defects in the device have been effectively passivated. From the device level, after adding the ionic compound passivator, the open circuit voltage of the wide bandgap perovskite device is increased from 1.24V to more than 1.30V, an increase of 7%. In the embodiments of the present invention, the photoelectric conversion efficiency of the wide bandgap perovskite device tested under AM 1.5G simulated sunlight reached 20.5%, an increase of 23%, and the open circuit voltage reached 1.33V. The lighting efficiency stability of the device can be significantly improved by more than 6 times.
[0036] The present invention proposes a method for improving the photographic stability of wide bandgap perovskite by inhibiting ion migration, which has high research and practical value for the preparation and application of wide bandgap perovskite photovoltaic cells. The method is simple and practical, does not change the preparation process of perovskite cells, and does not add additional process steps. Therefore, the present invention does not introduce new process parameters, operation time windows, etc. Only by adding a passivating agent that meets the above characteristics to the perovskite precursor solution, a wide bandgap perovskite cell with stable photophotography and higher efficiency can be produced. The strategy proposed by the present invention also provides an important reference idea for the research, development and industrial application of wide bandgap perovskites in perovskite / crystalline silicon tandem solar cells and all-perovskite tandem solar cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 Schematic diagram of the structure of a wide bandgap perovskite photovoltaic cell device;
[0038] Figure 2 A microscopic schematic diagram of the microscopic phase separation of wide bandgap perovskites and the inhibition of the phase separation process of thin films by the passivation of halogen ion vacancy defects;
[0039] Figure 3 This is the light stability curve of the wide bandgap perovskite film of control group 1;
[0040] Figure 4 This is the light stability curve of the wide bandgap perovskite film of control group 2;
[0041] Figure 5 To optimize the light stability curve of the wide bandgap perovskite film of group 1;
[0042] Figure 6 To optimize the light stability curve of the wide bandgap perovskite film of group 2;
[0043] Figure 7 To optimize the light stability curve of the wide bandgap perovskite film of group 3;
[0044] Figure 8 Current density-voltage test curves of wide bandgap perovskite films of optimization group 1, optimization group 2, optimization group 3 and control group 1 and control group 2;
[0045] Fig. 9 The light stability curves of wide bandgap perovskite devices of control group 1 and control group 2;
[0046] Fig.10 Light stability curves of wide bandgap perovskite devices of control group 1 and optimized group 1;
[0047] Fig.11 Light stability curves of wide bandgap perovskite devices of control group 1 and optimized group 2;
[0048] Fig.12 Light stability curves of wide bandgap perovskite devices of control group 1 and optimized group 3;
[0049] Fig.13 The curves of the open circuit voltage of the wide bandgap perovskite battery devices of the control group 1, the control group 2, the optimized group 1, the optimized group 2, and the optimized group 3 as a function of the light intensity;
[0050] Fig.14 To calculate the activation energy of ion movement of perovskite films in control group 1, control group 2, optimized group 1, optimized group 2, and optimized group 3;
[0051] Fig.15 These are the absorption spectrum intensity values of the wide bandgap perovskite films of control group 1, control group 2 and optimized group 1, optimized group 2, and optimized group 3 at 295nm. DETAILED DESCRIPTION
[0052] The following describes the preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0053] Example 1
[0054] Wide bandgap perovskite FA 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 Preparation of precursor solution:
[0055] FAI (formamidine iodide), CsI (cesium iodide), PbI2 (lead iodide) and PbBr2 (lead bromide) are mixed and dissolved in a mixed solvent (3:1) of DMF (N,N-dimethylformamide) and DMSO (dimethyl sulfoxide) according to a molar ratio to prepare a perovskite precursor with a molar concentration of 1.4 mol / L.
[0056] The perovskite precursor was placed in a glove box, heated and stirred for 6 h, and filtered using a 0.22 μm PTFE filter.
[0057] According to the molar ratio, 0.75 mol% sodium benzoate (i.e., 1.5 mg sodium benzoate) was added to each portion (1 mL) of the perovskite precursor. Stirring was performed for 1 hour to obtain a wide bandgap perovskite FA. 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 Precursor solution.
[0058] Example 2
[0059] The perovskite precursor was prepared and filtered in the same manner as in Example 1.
[0060] According to the molar ratio, 0.75 mol% potassium benzoate (i.e., 1.7 mg potassium benzoate) was added to each portion (1 mL) of the perovskite precursor. Stirring was performed for 1 hour to obtain a wide bandgap perovskite FA. 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 Precursor solution.
[0061] Example 3
[0062] The perovskite precursor was prepared and filtered in the same manner as in Example 1.
[0063] According to the molar ratio, 0.75 mol% of zinc benzoate (i.e., 3.2 mg of zinc benzoate) was added to each portion (1 mL) of the perovskite precursor. Stirring was performed for 1 hour to obtain a wide bandgap perovskite FA. 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 Precursor solution.
[0064] The wide bandgap perovskite FA obtained in Examples 1, 2 and 3 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 precursor solutions are respectively recorded as: optimization group 1, optimization group 2 and optimization group 3.
[0065] Comparative Example 1
[0066] Wide bandgap perovskite FA 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 Preparation of precursor solution:
[0067] FAI (formamidine iodide), CsI (cesium iodide), PbI2 (lead iodide) and PbBr2 (lead bromide) are mixed and dissolved in a mixed solvent (3:1) of DMF (N,N-dimethylformamide) and DMSO (dimethyl sulfoxide) according to a molar ratio to prepare a perovskite precursor with a molar concentration of 1.4 mol / L.
[0068] The perovskite precursor was placed in a glove box, heated and stirred for 6 h, and filtered using a 0.22 μm PTFE filter to obtain a wide bandgap perovskite FA. 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 Precursor solution.
[0069] Comparative Example 2
[0070] The perovskite precursor was prepared and filtered in the same manner as in Example 1.
[0071] According to the molar ratio, 0.75 mol% of phenylethylamine hydroiodide (i.e., 2.59 mg of phenylethylamine hydroiodide) was added to each portion (1 mL) of the perovskite precursor. Phenylethylamine hydroiodide is a commonly used passivation agent in the art, in which the phenylethylamine cation in the compound plays a major role. Stir thoroughly for 1 hour to obtain a wide bandgap perovskite FA. 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 Precursor solution.
[0072] The wide bandgap perovskite FA obtained in Comparative Examples 1 and 2 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 The precursor solutions were respectively recorded as: control group 1 and control group 2.
[0073] Device Example 1
[0074] (1) Treatment of ITO glass substrate and preparation of hole transport layer
[0075] The ITO substrate was ultrasonically cleaned in deionized water, acetone and isopropanol for 15 minutes each, and then the residual solvent on the substrate surface was blown dry with a nitrogen gun. Further, the ITO substrate was treated with ultraviolet ozone for more than 15 minutes to clean the organic matter that was not removed from the surface and improve the surface wettability of ITO. The aqueous dispersion of nickel oxide nanoparticles (concentration of 20 mg / mL) was spin-coated on the ITO surface at a spin-coating speed of 4000 rpm and a spin-coating time of 30 seconds. Afterwards, the film was placed on a 150°C heating table and annealed for 30 minutes. The isopropanol solution of (2-(9H-carbazole-9-yl)ethyl)phosphonic acid (2PACz) (concentration of 0.5 mg / mL) was spin-coated on the surface of the nickel oxide film, and the spin-coating speed and time were consistent with the nickel oxide layer, and the film was placed on a 100°C heating table and annealed for 10 minutes to complete the preparation of the composite hole transport layer.
[0076] (2) Preparation of perovskite films
[0077] The perovskite precursor solutions of control group 1, control group 2, optimized group 1, optimized group 2, and optimized group 3 were spin-coated on the surface of the composite hole transport layer film prepared in step (2) (spin coating parameters: rotation speed 3000-5000 rpm, time 30-40 seconds, and 100-300 μL anti-solvent chlorobenzene was added at 20-30 seconds). Afterwards, the film was placed on a heating table at 90-110° C. and annealed for 5-15 minutes to form a perovskite film.
[0078] (3) Preparation of electron transport layer and metal electrode layer by vacuum thermal evaporation
[0079] Fill the prepared perovskite film into the evaporation mask and place it in a vacuum evaporation chamber; evacuate the chamber until the gas pressure is less than 9×10 -5 After Pa, 20nm C60, 5nm BCP and 120nm Cu are thermally evaporated in sequence to complete the assembly process of the battery device.
[0080] Under AM 1.5G simulated sunlight, the photovoltaic cell performance parameters obtained from the tests of control group 1, control group 2, optimized group 1, optimized group 2, and optimized group 3 are shown in Table 1.
[0081] Table 1
[0082]
[0083]
[0084] As can be seen from Table 1, compared with the control group 1-2, the optimized group 1-3 using the passivator has better photovoltaic performance indicators. The reason is that the benzoate passivator can efficiently passivate the halogen vacancy defects in the perovskite film, significantly reduce the defect state density of the film, and effectively inhibit the non-radiative recombination loss caused by the defects, so that the device has a higher open circuit voltage, short circuit current, fill factor and photoelectric conversion efficiency.
[0085] The structure of the prepared wide bandgap perovskite photovoltaic cell device is as follows Figure 1 shown.
[0086] Figure 2 The microscopic schematic diagram shows the microscopic phase separation of wide bandgap perovskites and the inhibition of the phase separation process of thin films by passivation of halogen ion vacancy defects. Before the optimization with the passivator, there are many vacancy defects at the grain boundary, and after illumination, phase separation occurs to form iodine-rich regions and bromine-rich regions; after the passivator is used, the interface vacancy defects are filled by anions, and phase separation no longer occurs after illumination.
[0087] Wide bandgap perovskite FA prepared by Comparative Examples 1-2 and Examples 1-3 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 The light stability curves of the wide bandgap perovskite films obtained from the precursor solutions are shown in Figure 3-7 As shown. It can be seen that the wide bandgap perovskite film of Comparative Example 1 without the addition of a passivator has a red shift in the steady-state fluorescence peak of the film (moves to a region with a larger wavelength) when continuously illuminated, indicating that the film has undergone halogen ion phase separation and formed an iodine-rich phase perovskite with a smaller band gap. The steady-state fluorescence peak of the wide bandgap perovskite film of Comparative Example 2 with the addition of phenylethylamine hydroiodide still undergoes a red shift, indicating that the passivator used in Comparative Example 2 cannot inhibit the phase separation of wide bandgap halogen ions. After using a benzoate passivator in Examples 1-3, the steady-state fluorescence peak of the perovskite did not undergo a significant red shift, indicating that the halogen ions did not move significantly and form an iodine-rich phase region, and the phase stability of the wide bandgap perovskite was significantly improved.
[0088] Wide bandgap perovskite FA prepared by Comparative Examples 1-2 and Examples 1-3 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 The current density-voltage test curve of the wide bandgap perovskite film obtained from the precursor solution is shown in Figure 8As shown. It can be seen that the photovoltaic performance indicators such as open circuit voltage and short circuit current of the wide bandgap perovskite cells of Examples 1-3 are significantly better than those of Comparative Examples 1-2. This shows that after using benzoic acid passivators, defects are effectively passivated, non-radiative recombination losses are suppressed, and the device performance is further significantly improved.
[0089] Wide bandgap perovskite FA prepared by Comparative Examples 1-2 and Examples 1-3 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3 The light stability curves of the wide bandgap perovskite devices obtained from the precursor solution are shown in Figure 9-12 As shown. It can be seen that the time taken for the perovskite cells of Examples 1-3 to decay to 90% of the initial efficiency is significantly longer than that of Comparative Examples 1-2, that is, the Examples have a longer light stability life. The benzoate passivator improves the light stability of the wide bandgap perovskite by inhibiting the movement of halogen ions, which is manifested as a significant improvement in light stability at the photovoltaic device level.
[0090] Wide bandgap perovskite FA prepared by Comparative Examples 1-2 and Examples 1-3 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 The curve of the open circuit voltage of the wide bandgap perovskite device obtained by the precursor solution as a function of light intensity is shown in Fig.13 As shown. It can be seen that, on the one hand, under different light intensities, the optimized groups 1-3 all show higher open circuit voltages; on the other hand, the fitted straight line of the open circuit voltage of the optimized groups 1-3 has a smaller slope and a smaller ideal factor (closer to 1), indicating that the benzoic acid passivator can significantly reduce the defect density of the optimized groups 1-3 devices. This result proves that the benzoic acid passivator can efficiently passivate defects.
[0091] According to the Nernst-Einstein equation, the activation energy of ion migration of the perovskite film of the control group 1, the control group 2, the optimized group 1, the optimized group 2, and the optimized group 3 was calculated by using the variable temperature conductivity test, as shown in Fig.14 As shown. It can be seen that the activation energy of halogen ion movement in the optimization groups 1-3 is higher than that in the control groups 1-2, indicating that the energy barrier required for halogen ion movement is higher, that is, benzoic acid passivators can significantly inhibit the movement of halogen ions in perovskite films, and the films have better photochemical stability than the control groups 1-2. This result proves that benzoic acid passivators can significantly improve the phase stability of wide-bandgap perovskites.
[0092] The wide bandgap perovskite films of control group 1, control group 2 and optimized group 1, optimized group 2 and optimized group 3 were immersed in a transparent glass bottle filled with dichloromethane solvent and illuminated with the intensity of sunlight. The UV-visible absorption spectrum of dichloromethane solvent at 295nm was compared at 0h, 6h and 12h of illumination; the results are shown in Figure 2. Fig.15 As shown, it can be seen that under continuous illumination, the UV-visible absorption spectrum intensity of the control group 1-2 solution is significantly higher than that of the optimized group 1-3, indicating that the phase separation of the wide bandgap perovskite film in the control group 1-2 caused serious iodine ion oxidation and escape side reactions. However, due to the excellent phase stability, the optimized group 1-3 film did not undergo significant iodine ion oxidation and escape side reactions. This result further proves that benzoic acid passivators can significantly enhance the light stability of wide bandgap perovskites.
[0093] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A method for preparing a wide bandgap perovskite precursor solution, comprising the following steps: S1: Dissolve formamidine iodine, formamidine bromide, cesium iodide, cesium bromide, lead iodide and lead bromide in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide according to the molar ratio, heat and stir to obtain FA 0.8 Cs 0.2 Pb(Br 0.4 I 0.6 )3Perovskite precursor, filtration; S2: Add the passivator powder to the perovskite precursor and stir until dissolved to obtain a perovskite precursor solution. The passivator has the following characteristics: (1) The passivating agent is an ionic compound, wherein the anion valence is negative monovalent and the ion radius is greater than 0.22 nm, and does not contain halogen ions; (2) The passivating agent does not react chemically with the perovskite precursor solution, but its anion reacts with Pb 2+ Ions have strong binding forces; (3) The molecular weight of the passivating agent does not exceed 400 g / mol.
2. The preparation method according to claim 1, wherein The passivating agent is selected from metal benzoate, ammonium benzoate or a combination thereof.
3. The preparation method according to claim 1 or 2, wherein In step S1, the volume ratio of DMF and DMSO in the mixed solvent is 3:
1.
4. The preparation method according to claim 1 or 2, wherein: In step S2, the amount of the passivating agent added is 0.10-5.00 mol% of the molar mass of the perovskite precursor.
5. A method for preparing a wide bandgap perovskite solar cell, comprising the following steps: Step 1: ultrasonically clean the conductive glass ITO substrate with water, acetone and isopropanol in sequence; blow dry the cleaned ITO substrate with a nitrogen gun, and then treat the substrate with ultraviolet ozone for 15 minutes; spin-coat the aqueous dispersion of nickel oxide nanoparticles on the substrate, and move it to a heating table to complete annealing treatment to prepare a nickel oxide hole transport layer; Further, the solution of the monomolecular self-assembled layer is spin-coated and deposited on the nickel oxide hole transport layer, and a heating annealing treatment is performed to prepare a composite hole transport layer; Step 2: preparing a perovskite precursor solution according to the preparation method described in any one of claims 1 to 4; Step 3: Spin-coating the perovskite precursor solution on the surface of the composite hole transport layer prepared in step 1 by spin coating, and moving it to a heating table to complete annealing treatment to prepare a perovskite film; Step 4: Using vacuum thermal deposition technology, C60, BCP and Cu electrode materials are sequentially deposited on the surface of the perovskite film prepared in step 3 to obtain a wide bandgap perovskite solar cell.
6. The preparation method according to claim 5, wherein: In the step 1, the concentration of the nickel oxide nanoparticle aqueous dispersion is 10 mg / mL, the spin coating parameters are 4000 rpm, the time is 30 seconds, and the annealing conditions are 150° C., and the time is 30 minutes.
7. The preparation method according to claim 5, wherein: In the step three, the concentration of the perovskite precursor solution is 1.4 mol / L; the spin coating method is: one-step anti-solvent method, 5000 rpm, time 40 seconds, and 200 μL of chlorobenzene is added as anti-solvent at the 30th second, and the annealing condition is 100° C., time 10 minutes.
8. The preparation method according to claim 5, wherein: In the step 4, the deposition thicknesses of C60, BCP and Cu electrodes are 20 nm, 5 nm and 100 nm respectively.
9. A wide bandgap perovskite solar cell obtained by the preparation method according to any one of claims 5 to 8.
10. Use of the perovskite precursor solution obtained by the preparation method according to any one of claims 1 to 4 in the preparation of perovskite solar cells.
Citation Information
Patent Citations
Perovskite solar cell and preparation method thereof
CN116761446A
Surface-treated nickel oxide hole transport layer, perovskite solar cell and preparation method
CN117062452A
Broadband-gap perovskite solar cell based on 3-sulfopropyl acrylate potassium salt modification and preparation method and application thereof
CN118251108A